Pengembangan Perangkat Pembelajaran Berbasis Game Dengan Konteks Teka-Teki Silang Untuk Meningkatkan Kemampuan Numerasi - Athia Awwalia Salim; Sri Subarinah; Tabita Wahyu Triutami (Mandalika Mathematics and Educations Journal, 2026)
Abstract This study aims to develop game based learning tools using a crossword puzzle context to improve students’ numeracy skills. Numeracy abilities can be improved by increasing students understanding of mathematical concepts. Game Based Learning offers an interactive learning experience that can make students’ understanding mathematical concepts through a structured game process. This study employed a Research and Development (R&D) method using the ADDIE ( analysis, design, development, implementation, and evaluation). The subjects of the study were 34 seventh grade students of SMP Negeri 15 Mataram. The developed products include teaching modules, student worksheets (LKPD), and numeracy posttest based game with crossword puzzle. Data analysis techniques include analysis of validity, practicality and effectiveness using percentage and N-Gain tests. The results indicate that the developed learning tools are highly valid, with module validity of 89.74%, LKPD validity of 85.65%, and posttest validity of 85.42%. The practicality level reached 89.40% (very practical). Furthermore, the effectiveness test showed an increase in students’ numeracy skills, with the average score improved from 60.93 to 81.33, and an N-Gain of 0.52 in the moderate category. These findings indicate that game based learning tools with a crossword puzzle context are sufficiently effective in improving students’ numeracy skills.